Pictorial Glossary in Assamese - (:unkn) unknown (My University, 1994)
The words included in this glossary books are chosen on the basis of their picturability. These words consist of basic vocabulary items of the respective languages. These also include other frequent words which are used in day-to-day contexts in different walks of life.
Keywords: Assamese